Delayed Intraventricular Hemorrhage following a Ventriculoperitoneal Shunt Placement: Exploring the Surgical Anatomy of a Rare Complication. (8th November 2017) - Mavridis, Ioannis N.; Mitropoulos, Athanassios; Mantas, Constantinos; Karagianni, Aikaterini; Vlachos, Konstantinos
Abstract : Ventriculoperitoneal shunt (VPS) placement is one of the commoner neurosurgical procedures worldwide. The purpose of this article is to report a case of delayed intraventricular hemorrhage (IVH) following a VPS and to review the literature regarding anatomic factors that could potentially explain this rare complication. A 78-year-old man with normal pressure hydrocephalus, who underwent an uneventful right VPS placement, suffered from a catastrophic isolated IVH five days later. The reported cases of delayed intracerebral hemorrhage (ICH) following VPS are rare and those with IVH are even rarer. Potential factors of surgical anatomy that could cause delayed ICH/IVH following a VPS procedure include erosion of vasculature by catheter cannulation, multiple attempts at perforation, puncture of the choroid plexus, improper placement of the tubing within the brain parenchyma, VPS system revision, venous infarction, vascular malformations, head trauma, and brain tumors. Other causes include generalized convulsion, VPS system malfunction, increased intracranial or blood pressure, sudden intracranial hypotension, and bleeding disorders. According to the current literature, our case is the first reported delayed isolated IVH after a VPS placement so far. Neurosurgeons should be aware of the delayed ICH/IVH as a rare, potentially fatal complication of VPS, as well as of its risk factors.